The political economy of development aid: an investigation of three donor-funded HIV/AIDS programmes broadcast by Malawi television from 2004 to 2007 - Mulonya, Rodrick K A R (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
Development aid in most of the developing countries can sometimes compromise the principles of public service broadcasting (PSB). This may be true when reflected against the tension between donor financed programmes in Malawi and the mandate of Television Malawi (TVM). Although the donor intentions are noble, the strings attached to the funding are sometimes retrogressive to the role of PSBs. A case in point is how donors dictate terms on the HIV/Aids communication strategies at TVM. Producers receive money from donors with strings attached on how the money should be used and accounted for. If producers deviate they are sanctioned through withholding funding, shifting schedules and reducing the funding frequency. The donors also dictate who to interview on what subject, how to conduct capacity building. Some scholars have researched much on the impact of commercialisation of the media. This study is a departure from these traditional interferences; it interrogates the interest of philanthropy tendencies by international donors in the three chosen HIV/Aids programmes broadcast by TVM. The study investigates the extent of pressure exerted by donors on the producers of HIV/Aids programmes in Malawi. Thus, the study seeks to illicit specifics in the power relationship between the donor and the producer hence the study employs the political economy of development aid as applied to the public service broadcasting and communication for development. The study employed qualitative research methods and techniques (in-depth interviews, case study and document analysis). The study reveals how donor ideologies dominate the Aids messages-content output of the texts constructed. The study argues that cultural alienation of the Malawian audiences retards efforts of donors in combating HIV infection rate.
Keywords: Economic assistance -- Malawi -- Management; Public service television programs -- Malawi; AIDS (Disease) and mass media -- Malawi; HIV infections -- Information services -- Malawi; Communication in public health -- Malawi; Economic assistance -- Social aspects -- Malawi; Malawi -- Social conditions; Mass media -- Social aspects -- Malawi; Mass media criticism -- Malawi